Design and energy utilization of electro-hydrostatic hydraulic hybrid system for battery bus. (February 2021) - Chen, Guanpeng; Liu, Huanlong
In order to solve the problems of large peak torque and short battery life when the city battery bus starts or accelerates, a new electro-hydrostatic hydraulic hybrid powertrain is designed in this paper that can operate efficiently in all speed conditions with a certain type of electric bus running in Chengdu. The improvement of comprehensive energy efficiency of power system by switching between different power modes under typical operating conditions is studied. Through the co-simulation of AMESim and MATLAB/Simulink-stateflow software, the vehicle and control models are established and the rule-based dynamic optimal energy management strategy is set. The dynamic performance and energy utilization characteristics of New European Driving Cycle and the cycle condition of investigation under actual driving environments are analyzed. The core problems of energy coupling of electro-hydrostatic hydraulic hybrid powertrain are studied experimentally to verify the correctness of the design thought and simulation model. The results show that under the premise of satisfying the dynamic performance, the designed electro-hydrostatic hydraulic hybrid system can effectively improve the overall average efficiency of operating point of the electric motor and greatly reduce the peak torque. The peak torque is reduced by 36.4% and the battery power consumed by the selected cycle is reduced by 33.98% under New European Driving Cycle conditions. Under the actual cycle conditions, the peak torque is reduced by 28.9%, and the battery power consumed by the selected cycle is reduced by 32.3%.